Selenium Isotope Studies in Plants - Development and Validation of a Novel Geochemical Tool and its Application to Organic Samples - Banning, Helena (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Angewandte Geowissenschaften, 2017)
Selenium (Se), being an essential nutrient and a toxin, enters the food chain mainly via plants. Selenium isotope signatures were proved to be an excellent redox tracer, making it a promising tool for the exploration of the Se cycle in plants. The analytical method is sensitive on organic samples and requires particular preparation methods, which were developed and validated in this study. Plant cultivation setups revealed the applicability of these methods to trace plant internal processes.